Artificial Blood: The History and Current Perspectives of Blood Substitutes - Khan, Fahad (Discoveries (Craiova), 2020)
Blood transfusions are one of the most common procedures performed in hospitalized patients. Yet, despite all of the measures taken to ensure the safety of the blood supply, there are known risks associated with transfusions, including infectious and noninfectious complications. Meanwhile, issues with blood product availability, the need for compatibility testing, and the storage and transport requirements of blood products, have presented challenges for the administration of blood transfusions. Additionally, there are individuals who do not accept blood transfusions (e.g., Jehovah’s Witnesses). Therefore, there is a need to develop alternative agents that can reliably and safely replace blood. However, although there have been many attempts to develop blood substitutes over the years, there are currently no such products available that have been approved by the United States Food and Drug Administration (FDA). However, a more-recently developed hemoglobin-based oxygen carrier has shown promise in early clinical trials and has achieved the status of “Orphan Drug” under the FDA.